2023
DOI: 10.3390/ijms24021145
|View full text |Cite
|
Sign up to set email alerts
|

Functional Relationships between Long Non-Coding RNAs and Estrogen Receptor Alpha: A New Frontier in Hormone-Responsive Breast Cancer Management

Abstract: In the complex and articulated machinery of the human genome, less than 2% of the transcriptome encodes for proteins, while at least 75% is actively transcribed into non-coding RNAs (ncRNAs). Among the non-coding transcripts, those ≥200 nucleotides long (lncRNAs) are receiving growing attention for their involvement in human diseases, particularly cancer. Genomic studies have revealed the multiplicity of processes, including neoplastic transformation and tumor progression, in which lncRNAs are involved by regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 147 publications
0
3
0
Order By: Relevance
“…The HGC-27 cell line has been widely used in studies on gastric cancer progression, improvements in therapeutic strategies, and drug resistance 14 16 . HGC-27-LR cells were established using a classical approach to subjecting cells to long-term drug gradient pressure in vitro 9 . Subsequently, CCK-8 analysis was performed to determine any potential alterations in the sensitivity of HGC-27 cells to lapatinib.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HGC-27 cell line has been widely used in studies on gastric cancer progression, improvements in therapeutic strategies, and drug resistance 14 16 . HGC-27-LR cells were established using a classical approach to subjecting cells to long-term drug gradient pressure in vitro 9 . Subsequently, CCK-8 analysis was performed to determine any potential alterations in the sensitivity of HGC-27 cells to lapatinib.…”
Section: Resultsmentioning
confidence: 99%
“…The association between long non-coding RNAs and drug resistance in tumor-targeted therapy is currently a hot topic of research 9 11 . LncRNAs are aberrantly expressed at different stages of gastric cancer progression, and a few studies have reported mechanisms by which lncRNAs regulate lapatinib-induced drug resistance in gastric cancer; hence, lncRNAs associated with drug resistance may potentially be targeted for personalized therapeutic strategies 11 13 .…”
Section: Introductionmentioning
confidence: 99%
“…What distinguishes them is their substantial length, often exceeding 200 nucleotides. Remarkably, lncRNAs constitute a major portion of the ncRNA landscape, accounting for a substantial percentage, typically ranging from 80 % to 90 % of all ncRNAs [ 9 ]. Their abundance underscores their importance in cellular processes.…”
Section: Lncrnamentioning
confidence: 99%